Strategi Public Relations dalam Mempertahankan Citra Positif: Studi Kasus RRI Bandung - Annisa Oktaviani Dewi; Maman Suherman (UNISBA Press, 2022)
Abstract. Various kinds of Private Radio Competitors made RRI Radio Government devise a strategy to maintain its image so that it remains the leading one. The many public stigmas regarding RRI's image seemingly old-fashioned and left behind give researchers a deep sense of curiosity about the strategies used by RRI Bandung PR. Therefore, the author conducted a study entitled